TUTURAN MEMUJI OLEH GURU PEREMPUAN DALAM INTERAKSI PEMBELAJARAN BAHASA INDONESIA - Pandu Meidian Pratama; Anang Santoso; Martutik Martutik (Graduate School of Universitas Negeri Malang, 2016)
Research on speech acts of female teachers in Indonesian language learning interaction is based on the patterns of communication that occurs between teachers and students in the context of learning in the classroom. The purpose of this study was to describe (1) the nature praised the speech act, (2) functions praised the speech act, and (3) the mode of speech act of praise spoken by women who work as teachers Indonesian. In addition to describing the form, function, and mode of speech acts raving, this study also tried to describe the use of language women are seen from the perspective of culture and the features it uses, namely (1) tag question, (2) avoidance of strong swear words, (3) superpolite form, (4) empathic stress, and (5) intensifiers.Penelitian tentang tuturan guru perempuan dalam interaksi pembelajaran bahasa Indonesia ini dilandasi oleh pola komunikasi yang terjadi antara guru dan siswa dalam konteks pembelajaran di kelas. Penelitian ini memiliki tujuan untuk mendeskripsikan (1) wujud tuturan memuji, (2) fungsi tuturan memuji, dan (3) modus tuturan memuji yang dituturkan oleh kaum perempuan yang berprofesi sebagai guru bahasa Indonesia. Selain mendeskripsikan wujud, fungsi, dan modus tuturan memuji, penelitian ini juga berusaha mendeskripsikan penggunaan bahasa perempuan dipandang dari sudut pandang budaya dan fitur-fitur yang digunakannya, yaitu (1) tag question, (2) avoidance of strong swear words, (3) superpolite form, (4) emphatic stress, dan (5) intensifiers.